PENGARUH KEPEMIMPINAN DAN KOMPETENSI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA PEGAWAI DI KEMENTERIAN AGAMA KABUPATEN PADANG LAWAS UTARA - Arjuna Pipian Harahap; Fachruddin Siregar; Arsan Aligami; Emilyati .; Nurhaini . (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
Formulation of problems in this study is how the influence of leadership on employee work motivation, how competency influences employee work motivation, how leadership influences employee performance, how competency influences employee performance and how work motivation affects employee performance in the Ministry of Religious Affairs North Padang Lawas Regency. This research aims to find out and analyze the influence of leadership on employee work motivation, the influence of competence on employee work motivation, the influence of leadership on employee performance, the influence of competence on employee performance and the influence of work motivation on employee performance in the Ministry of Religious Affairs North Padang Lawas Regency.This research is a descriptive quantitative research. Data collection techniques are carried out through interviews, lists of questions and documentation studies. samples in the study amounted to all employees in the Ministry of Religious Affairs North Padang Lawas Regency as many as 68 people. This study has three exogenous variables namely leadership (X1), competence (X2) and motivation (X3) and one endogenous variable namely employee performance (Y). Path analysis is used to look at the influence of exogenous variables on endogenous variables through other exogenous variables and measure the direct and indirect influence of a variable on other variables. After conducting normality and homogeneity test, this research was continued by doing path analysis.  There is a positive and significant influence between the leadership on the motivation at the Office of the Ministry of Religious Affairs of North Padang Lawas. Based on the results of the path analysis obtained a calculated t value of 2,052 at a significance of 0.044. There is a positive and significant influence between competencies on motivation at the Office of the Ministry of Religious Affairs of North Padang Lawas. Based on the results of the track analysis obtained a calculated t value of 2,872 at a significance of 0.006. There is a positive and significant influence between the leadership on the performance at the Office of the Ministry of Religious Affairs of North Padang Lawas. Based on the results of the track analysis obtained a calculated t value of 2,892 at a significance of 0.005. There is a positive and significant influence between competencies on performance at the Office of the Ministry of Religious Affairs of North Padang Lawas. Based on the results of the path analysis obtained a calculated t value of 3,332 at a significance of 0.001. Based on the results of the track analysis obtained t calculated value of 3,489 at a significance of 0.001, there is a positive and significant influence between motivation to the performance at the Office of the Ministry of Religious Affairs North Padang Lawas..